2020
DOI: 10.1111/joor.13093
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Saxon test for patients with hyposalivation without Sjögren’s syndrome

Abstract: Background: Dry mouth is associated with salivary gland hypofunction, which may result from several conditions such as Sjögren's syndrome (SS), head and neck cancers, and side effects of medications. The Saxon test is a useful diagnostic method for hyposalivation in clinical settings. However, previous reports indicate that the test has mostly been used for patients with SS. Objective(s): In the present study, we focused on patients with dry mouth who were not diagnosed with SS (patients without SS). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Using multiple regression analysis, we examined the factors affecting the Saxon test score for patients. Our results showed that age and sex significantly affected the Saxon test score; this data showed as same as the past study results [8]. The elderly patients showed harder hyposalivation than young patients except the factor of the medication.…”
Section: Discussion/conclusionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using multiple regression analysis, we examined the factors affecting the Saxon test score for patients. Our results showed that age and sex significantly affected the Saxon test score; this data showed as same as the past study results [8]. The elderly patients showed harder hyposalivation than young patients except the factor of the medication.…”
Section: Discussion/conclusionsupporting
confidence: 91%
“…For drug-induced xerostomia, using the lowest effective dose or switching to an alternative medication may help. However, there are few considerations regarding the underlying situation and the patients' intake of medicines for xerostomia [7,8]. Xerostomia is a common complaint observed in the elderly who often complain of oral dryness as a result of underlying diseases and as a side effect of taking drugs [9].…”
Section: Introductionmentioning
confidence: 99%
“…The moisture levels of the oral mucosa were measured using an oral moisture-checking device (Mucus®, LIFE Co.). The device analyzes water maintenance of the mucous membrane 13 . The oral moisture score of the buccal mucosa was repeated thrice, and the median value was selected.…”
Section: Opportunistic Bacterial Count Measurementmentioning
confidence: 99%
“…In typical clinical practice, in addition to the distinct signs of dry mouth (which Jager et al simplified into a clinical oral dryness score [ 6 ] for rapid screening), various quantitative tests of salivary excretion have been proposed to evaluate dry mouth and can be divided into the following five categories, as reported by Löfgren et al [ 7 ]: Secretion tests, including sialometry, the oral Schirmer’s test [ 8 ], the Saxon test [ 9 ], and methods that explores changes in salivary composition [ 10 ]; Mucosal/surface tests such as measurements of mucosal saliva thickness [ 11 ] or salivary smears [ 12 ], or measurements of the impedance of oral mucosa on a moisture-checking device [ 13 ]; “Functional” tests performed by using the dissolution of candy [ 14 ] or wafers [ 15 ]; Glandular morphology, including sonography [ 16 ], magnetic resonance imaging (MRI) [ 17 ], sialography, and salivary gland scintigraphy (sialoscintigraphy); Questionnaires, interviews, or a combination of both [ 18 ]. …”
Section: Introductionmentioning
confidence: 99%
“…Secretion tests, including sialometry, the oral Schirmer’s test [ 8 ], the Saxon test [ 9 ], and methods that explores changes in salivary composition [ 10 ];…”
Section: Introductionmentioning
confidence: 99%